Адольф Павлович Юшкевич (до 100-річчя від дня народження) - Добровольський, В.О. (Наука та наукознавство, 2006)
Статья посвящена памяти одного из наиболее известных историков математики XX столетия, выдающегося отечественного ученого, заслуженного деятеля науки Российской Федерации, действительного члена Международной академии истории науки, уроженца Украины Адольфа Павловича Юшкевича. The paper is dedicated to the memory of Adolf P.Yushkevich, one of the most distinguished historians of mathematics of XX century, an eminent national scientist, a honored scientist of the Russian Federation, an acting member of the International Academy of Science History, a native of Ukraine.